(untitled) (Revista Argentina de Musicología, 2018)
In this paper the work of the Argentinian musician and composer Eduardo Lagos is examined. The analysis of some of his most emblematic music and the study of the context where he produced his music, allow us to reveal the ground-breaking character of his style, the fusion between folk music and jazz, and the peculiarity of his musical practice where a distinctive playful feature is outlined.